Early childhood practice : Froebel today - Bruce, Tina. (London : SAGE, 2012)
"There can be little doubt that the education of the very young provides an essential foundation for all that follows, and the nature of that education is critical. This book locates Froebelian practice in current practice, through a wealth of examples from contemporary settings. The book brings together contributions from distinguished primary and early childhood practitioners, who show how they have used educational methods advocated by Froebel. Stressing the importance of outdoor play, they explore the Froebelian principles of: Play ; Learning through firsthand experience ; Parent partnership and community in early childhood ; Practitioners supporting children's interests and learning ; Finger rhymes and action songs ; Movement ; The garden and forests ; Wooden blockplay ; Use of clay, paint, junk modeling, construction kits."--Publisher's website.
The Whole Child / Tina Bruce ; Family, Community and the Wider World / Tina Bruce ; The Changing of the Seasons in the Child Garden / Stella Brown ; Adventurous and Challenging Play Outdoors / Helen Tovey ; Offering Children First Hand Experiences through Forest School: Relating to and Learning about Nature / Lynn McNair ; The Time-Honoured Froebelian Tradition of Learning out of Doors / Jane Read ; Family Songs in the Froebelian Tradition / Maureen Baker ; The Importance of Hand and Finger Rhymes: A Froebelian Approach to Early Literacy / Jenny Spratt ; Froebel's Mother Songs Today / Marjorie Ouvry ; Gifts and Occupations: Froebel's Gifts (Wooden Block Play) and Occupations (Construction and Workshop Experiences) Today / Jane Whinnett ; Froebelian Methods in the Modern World: A Case of Cooking / Chris McCormick ; Bringing together Froebelian Principles and Practices / Tina Bruce.
Includes bibliographical references.
Keywords: Fröbel, Friedrich, -- 1782-1852.; Kindergarten; Early childhood education -- Philosophy